Personal constraints’ impact on cognitive distortions in persons deprived of liberty - Noel alcas Zapata, Jessica Paola Palacios Garay, Máximo Abel Rodríguez Taboada,; Juan Carlos Chumacero Calle, Mitchell Alberto Alarcón Díaz, Yanina Gallardo-Lolandes, (Opción, 2020)
The objective of the research was to determine the incidence of personal conditions on the cognitive distortions of persons deprived of liberty for crimes of violence against women via the hypothetical deductive method. The results showed the incidence of personal conditioning on the cognitive distortions of these individuals sanctioned for acts of violence against women. In conclusion, for the treatment of persons who have committed acts of violence against women in prisons, following investigations and the results of the studies carried out by the Ministry of Justice, the prison system must be adapted to the needs of the prison population.